INFORMATIVENESS OF BIOCHEMICAL INDICATORS IN THE DIAGNOSIS OF VIRAL HEPATITIS B AND C IN PREGNANT WOMEN - Sariyeva, E.G.; Gafarov, I.A. (World of Medicine and Biology, 2022)
The choice of the correct treatment tactics for HBV, HCV-infections is based on biochemical and immunological indicators. In this regard, the development of programs on a mathematical basis can be considered a rational and correct approach to solving the diagnostic problem. The aim of the research was to assess the informativeness of additional laboratory indicators in the diagnosis of viral hepatitis B and C in pregnant women. The investigation included 150 pregnant women: the main group – 100 pregnant women with hepatitis B and C, the control group – 50 practically healthy pregnant women. Were carried out serological studies, polymerase chain reaction, biochemical, immunological blood tests. The results of the study showed that, among the studied indicators, apolipoprotein A1 and IgG have the highest sensitivity and overall diagnostic value, IgG, IgM and microglobulin-в2 have the highest specificity, and the indicators of microglobulin-b2, IgG and IgM. Apolipoprotein A1 and IgG have the highest negative efficacy scores. The ratio of the accuracy of positive and negative results allows the use of indicators of total cholesterol, apolipoprotein A1, low-density lipoproteins, microglobulin-в2, iron, C-reactive protein, IgG, IgM as auxiliary diagnostic biomarkers of infection of pregnant women with hepatitis B and C.